2023
DOI: 10.1002/dev.22369
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maternal stress and the severity of autism spectrum disorder: A cross‐sectional study

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder linked to several genetic and environmental factors including antenatal stress. Hence, we aimed to examine whether a mother's stress during pregnancy is associated with the severity of autism spectrum disorder in children. The study was conducted with 459 mothers of children with autism (aged 2-14 years) who were attending rehabilitation and educational centers in the two major cities of Makkah and Jeddah in Saudi Arabia.Environmental factors, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 92 publications
1
1
0
Order By: Relevance
“…Participants of the study experienced prenatal stress; ASD cases were compered to controls in terms of family history of psychological disorders. Findings of this study in line with previous studies found linkage between prenatal stress and odds of ASD (Ward,1990;Beversdorf et al, 2005;Varcin, et al, 2017;Alamoudi, et al, 2023;Seebeck, Sznajder, & Kjerulff, 2023) .These studies had several limitations include: (1) depending on retrospective recall that may lead to biased information, (2) mothers of children with ASD may frequently experience stressful life events even they are not pregnant, (3) as a result they may expose to stressor in all pregnancies regardless their children have ASD, (4) there were several confounding factors that did not controlled such as problems related to postnatal environments (Kinney, et al, 2008). Present study considered these limitations by using design overcame these difficulties.…”
Section: Discussionsupporting
confidence: 92%
“…Participants of the study experienced prenatal stress; ASD cases were compered to controls in terms of family history of psychological disorders. Findings of this study in line with previous studies found linkage between prenatal stress and odds of ASD (Ward,1990;Beversdorf et al, 2005;Varcin, et al, 2017;Alamoudi, et al, 2023;Seebeck, Sznajder, & Kjerulff, 2023) .These studies had several limitations include: (1) depending on retrospective recall that may lead to biased information, (2) mothers of children with ASD may frequently experience stressful life events even they are not pregnant, (3) as a result they may expose to stressor in all pregnancies regardless their children have ASD, (4) there were several confounding factors that did not controlled such as problems related to postnatal environments (Kinney, et al, 2008). Present study considered these limitations by using design overcame these difficulties.…”
Section: Discussionsupporting
confidence: 92%
“…Result showed that the moderate severity in prenatal life events was associated with ASD than history of no stress(p = .031; OR: 3.82). 13 Similar findings were found in a case control study done by Zhang et al in China. In their study 95 children were taken as case and 95 children as control.…”
Section: Discussionsupporting
confidence: 85%
“…11 Some studies showed environmental stress, threatened abortion, PET, diabetes, cardiac problem, systemic disease during pregnancy, multiple pregnancy, male child, prolonged labour, preterm birth, low birth weight , neonatal seizure, delayed cry, higher paternal and maternal age at birth as risk factors of ASD. 3,9,[12][13][14][15] Many factors make ASD difficult to understand and manage . Thus, recent research has focused on identifying specific biological abnormalities for diagnostic purposes as well as to measure changes resulting from treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Algumas variantes foram refutadas pelos especialistas como responsáveis pelo aumento de autismo, como é o caso da exposição a metais pesados, que não será investigada pelo presente estudo (PORTOLESE et al, 2017). Enquanto isso, outras já foram reconhecidas e comprovadas, como a exposição materna a poluentes, medicamentos usados durante a gravidez, além da idade parental avançada (FRYE et al, 2021;ALAMOUDI et al, 2023). Como exemplo, em estudos de meta-análise, foi demonstrado o aumento do risco em 18 a 21% quando há aumento de 10 anos na idade materna e paterna respectivamente (BEVERSDORF et al, 2018;BEVERSDORF et al, 2005;KINNEY et al, 2007;HECHT et al, 2016;MODABBERNIA;VELTHORST;REICHENBERG, 2017).…”
Section: Listas De Figuras Tabelas Quadros Gráficos Símbolos E Abrevi...unclassified